1999
DOI: 10.1046/j.1365-2567.1999.00665.x
|View full text |Cite
|
Sign up to set email alerts
|

Extrathymic derivation of gut lymphocytes in parabiotic mice

Abstract: In adult mice, c-kit+ stem cells have recently been found in their liver, intestine and appendix, where extrathymic T cells are generated. A major population of such thymus-independent subsets among intraepithelial lymphocytes is T-cell receptor (TCR)gamma delta+ CD4- CD8alpha alpha+(beta-) cells, but the origins of other lymphocyte subsets are still controversial. In this study, we examined what type of lymphocyte subsets were produced in situ by such stem cells in the small intestine, large intestine and app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 26 publications
4
33
0
Order By: Relevance
“…In this scenario, the highly motile and mobile peripheral gd T cells of the cotransplanted MLNs completely exchanged with their respective host counterparts during a period of 7 d. At the same time, the analysis of the transplanted intestines clearly showed that there was no redistribution of graft and host gd iIEL cells taking place. Of note, the use of TcrdH2BeGFP reporter mice allowed us to unambiguously identify bona fide gd T cells and revealed an even lower level of cellular exchange between donor and graft gd iIELs than expected from previous studies using parabiotic mice (59,60). Importantly, most probably due to their capacity of local selfrenewal, environmental niches for intestinal gd T cells were occupied in this experimental model.…”
Section: Discussionmentioning
confidence: 60%
“…In this scenario, the highly motile and mobile peripheral gd T cells of the cotransplanted MLNs completely exchanged with their respective host counterparts during a period of 7 d. At the same time, the analysis of the transplanted intestines clearly showed that there was no redistribution of graft and host gd iIEL cells taking place. Of note, the use of TcrdH2BeGFP reporter mice allowed us to unambiguously identify bona fide gd T cells and revealed an even lower level of cellular exchange between donor and graft gd iIELs than expected from previous studies using parabiotic mice (59,60). Importantly, most probably due to their capacity of local selfrenewal, environmental niches for intestinal gd T cells were occupied in this experimental model.…”
Section: Discussionmentioning
confidence: 60%
“…[25][26][27] In the present study, for the first time, we found a large expansion of cd T cells with the phenotype DN CD4 -CD8 -and B220 + in DBA/2 mice after malarial infection. In addition to the DN phenotype, the expression of the B220 + B-cell marker on T cells was unique.…”
Section: Discussionmentioning
confidence: 74%
“…Extrathymic pathways of T cell differentiation exist in the intestine and liver (Sato et al 1995), where T cell populations may arise from their own preexisting precursor cells rather than thymus (Sugahara et al 1999). Extrathymic T cells are also present in the uterus and exocrine glands, for example, salivary gland (Abo 2001 (int) , and presence of self-reactive clones (Abo 1993;Ohteki et al 1992).…”
Section: Liver Involvement In Extrathymic T Cell Productionmentioning
confidence: 99%